2010
DOI: 10.19030/ajbe.v3i6.436
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Based Learning On Students Critical Thinking Skills In Teaching Business Education In Malaysia: A Literature Review

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt; mso-pagination: none; mso-layout-grid-align: none;"><span style="font-family: Times New Roman;"><span style="font-size: 10pt; mso-ansi-language: EN-MY;" lang="EN-MY">This review forms the background </span><span style="font-size: 10pt;" lang="EN-GB">to explore and to gain empirical support among lecturers to improve the students’ critical thinking skills in business education courses in Malaysia, in which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 34 publications
1
53
1
8
Order By: Relevance
“…It is related to a perceived need to deal with the information explosion in this era. However these skills are neither inborn nor naturally acquired, yet must be trained in students (Changwong, Sukkamart, & Sisan, 2018;Mangena & Chabeli, 2005;Su, Ricci, & Mnatsakanian, 2016;Suarniati, Hidayah, & Handarini, 2018;Ulger, 2018;Visande, 2014;Zabit, 2010). Based on equation (1), the result indicated that analytical skill has the highest contribution to students' critical thinking skills.…”
Section: Classical Assumption Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is related to a perceived need to deal with the information explosion in this era. However these skills are neither inborn nor naturally acquired, yet must be trained in students (Changwong, Sukkamart, & Sisan, 2018;Mangena & Chabeli, 2005;Su, Ricci, & Mnatsakanian, 2016;Suarniati, Hidayah, & Handarini, 2018;Ulger, 2018;Visande, 2014;Zabit, 2010). Based on equation (1), the result indicated that analytical skill has the highest contribution to students' critical thinking skills.…”
Section: Classical Assumption Testsmentioning
confidence: 99%
“…This result could be a basic reference in designing the learning process which is able to empower the critical thinking skills of students. For example, educators can accommodate students' critical skill using the scientific process (Gultepe, 2016), such as problem-based learning (Birgili, 2015;Ulger, 2018;Zabit, 2010).…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Problem-based learning has been advanced in higher education as a powerful instructional approach to promoting deep and meaningful learning (Allen and Rooney 1998;Esteban and Canado 2004;Strobel and Barneveld 2009). Previous studies have documented evidence of its effects on promoting deep learning (Huang and Wang 2012), self-directed learning (Hmelo-Silver 2004), and higher-order thinking skills (Zabit 2010), as well as on language use embedded in certain domain areas where English is used as a second or foreign language (Hunter, Vickery, and Smyth 2010;Wood and Head 2004). The PBL approach provides authentic business contexts and opportunities for students to work in small groups to analyse and solve real problems (Haines 1989;Lee 2002), which enables the co-construction of business knowledge through the use of English as a foreign language (Grosse 1988).…”
Section: Student Learning In Problem-based Learning In International mentioning
confidence: 99%
“…Modern cognitivists have developed new trends and theories that provide theoretical models for explaining and conceptualizing reading comprehension by utilizing a set of related concepts, such as critical thinking, prior knowledge, inference-making, and metacognitive skills (Limbach and Waugh, 2010;Zabit, 2010). Among these trends is schema theory, which is considered to be a theory about knowledge: how knowledge is represented and organized, and how that representation and organization facilitates the use of a reader's prior knowledge to improve reading comprehension.…”
Section: Introductionmentioning
confidence: 99%